Analysis of Environmental Risk Factors for Leprosy in Indonesian Society: Meta-Analysis - Guguk Fadjari Ari Edi; R Azizah (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Indonesia is still the third largest contributor of new cases of leprosy in the world. The purpose of this study was to analyze the risk factors for the influence of humidity, occupancy density, and personal hygiene on the incidence of leprosy. Using the Meta-Analytic Method with the PICOS technique. Some of the data sources used are Google Scholar, Research Gate and Plos ONE by looking at keywords such as "Humidity", "Personal Hygiene", and "Occupancy Density". There were 71 articles. The Random Effect value with 95% CI variable humidity is 2.13 with a value range of 1.35 – 2.92. The forest plot results show the value of pooled PR = e2.13 = 8.415. The Random Effect value with 95% CI for the individual hygiene variable is 1.84 with a range value of 1.59-2.10. the results of the forest plot show the value of pooled PR = e1.84 = 6.926. The Random Effect value with 95% CI variable occupancy density is 1.75 with a value range of 1.36-2.14. forest plot results show the value of pooled PR = e1.75 = 5.754. Humidity has greates risk of causing leprosy. Meanwhile, Personal hygiene has a 6.926 times greater risk of causing leprosy. Residential density is at risk 5,754 times greater for experiencing leprosy. The factors that most influence the incidence of leprosy are humidity followed by personal hygiene and occupancy density. It is recommended that further research use qualitative data to look deeper into the intermediary factors that cause leprosy.